The Relationship Between Neuroticism Fit and General Well-Being: The Mediating Effect of Psychological Resilience - Ran Hao (Frontiers in Psychology, 2019)
BackgroundThe dominance complementarity theory argues that effective and continuing interpersonal relationships require complementary dominance and submission values. This theory has been widely applied to interpersonal interaction studies. Although studies have demonstrated the correlation between neurotic personality traits and general well-being (GWB) in older adults, the interpersonal interactions and psychological mechanisms underlying this effect remain unclear.AimUsing this theory, we explored the effect of the neuroticism fit between older adults and primary caregivers on older adults’ GWB and examined the mediating role of psychological resilience (PR).MethodsOne hundred sixty-one dyads of older adults and primary caregivers in nursing homes completed scales that included the Eysenck Personality Questionnaire-Revised Short Scale, the 10-Item Connor-Davidson Resilience Scale, and the GWB Schedule. We performed a cross-level polynomial regression, response surface modeling and mediating effect test to analyze the data.Results(1) Older adults’ GWB was higher when the neuroticism fit between older adults and primary caregivers was incongruent rather than congruent (p < 0.01). (2) In cases of incongruence, older adults’ GWB was higher only if their neuroticism was lower than that of their primary caregivers (p < 0.01). (3) In cases of congruence, older adults’ GWB was higher when the neuroticism of both sides was lower (p < 0.01). (4) PR partially mediated the relationship between neuroticism incongruence and older adults’ GWB (indirect effect = 0.14, p < 0.01).ConclusionThe neuroticism incongruence between older adults and primary caregivers was beneficial to older adults’ GWB and was partially mediated by PR.